2016
DOI: 10.1063/1.4961686
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Variation after response in quantum Monte Carlo

Abstract: We present a new method for modeling electronically excited states that overcomes a key failing of linear response theory by allowing the underlying ground state ansatz to relax in the presence of an excitation. The method is variational, has a cost similar to ground state variational Monte Carlo, and admits both open and periodic boundary conditions. We present preliminary numerical results showing that, when paired with the Jastrow antisymmetric geminal power ansatz, the variationafter-response formalism del… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…The previous studies through using the single‐ and multideterminant trial wave functions show that the QMC methods could provide an accurate description for both the ground and excited state properties . However, these studies have revealed that there is a strong dependence between the accuracy of the obtained energies and the quality of the trial wave function in the ground and excited states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies through using the single‐ and multideterminant trial wave functions show that the QMC methods could provide an accurate description for both the ground and excited state properties . However, these studies have revealed that there is a strong dependence between the accuracy of the obtained energies and the quality of the trial wave function in the ground and excited states.…”
Section: Introductionmentioning
confidence: 99%
“…). Additionally, Eric Neuscamman proposed “Variation after response “method [9] in which it was claimed that the obtained results are more accurate than those of the former one.…”
Section: Introductionmentioning
confidence: 99%
“…We recently introduced an ansatz that we call the finite-difference linear response (FDLR) wave function 16,17 . The FDLR approach allows one to consider a general wave function, and to construct a significantly more flexible ansatz in its linear response space.…”
Section: Introductionmentioning
confidence: 99%
“…This ansatz follows the recently-introduced variation-afterresponse (VAR) approach. 33 Specifically, we consider the linear response space of an optimizable determinant, which contains the full flexibility of a configuration interaction singles (CIS) wave function, 34 together with orbital rotations. Using a finite-difference approximation, this wave function may be expressed efficiently as a difference of two Slater-Jastrow functions.…”
Section: Introductionmentioning
confidence: 99%